A democratização nos cursos de elevado prestígio social na UFPB: acesso e permanência dos estudantes cotistas - COSTA, Nayara Tatianna Santos da (2017)
Screen research reiterates the responsibility of University in the process of democratization of High Social prestige, and the reflections on the mechanisms of permanence from the shareholders. Have assumed, that the choices of students still get along due to your cultural capital, the habitus of a social group and its chances of future success, as well as the overall structure of the education system. Aimed to analyze the policy of quotas on UFPB regarding democratization of access and permanence of the shareholders in the courses of high social prestige of the campus I of UFPB. He enrolled in a quantitative and qualitative approach of research, whose investigation broke the look on access, from the enrolment indicators in the CEPS and CBPS of 2011-2015 analyzed by SPSS software, which had a higher concentration of students respectively in pedagogy, law, medicine, civil engineering, nutrition and physical. About the permanence, sought to understand the nuances of performance of shareholders through the CRAs, beyond their trajectories, social origins and the mechanisms of student assistance offered by UFPB from students ' shareholders look of CEPS, using the semi-structured interviews and thematic analysis of content of Bardin. Was on the concepts of cultural capital, field and habitus in Bourdieu, and discussed the democratization whereas access, permanence and the concept of quality in education. Argued that the democratization of public higher education took place primarily via careers considered of lesser social prestige, and the area of Humanities in particular, although the study recognizes the role of the law of quotas in the reconfiguration of the profile of the students present in the most prestigious courses.